Refinement of Strengths Instruction in a Pharmacy Curriculum Over Eight Years - Janke, Kristin K. (American Journal of Pharmaceutical Education, 2011)
OBJECTIVE: To develop, refine, and integrate introductory-level strengths instruction within a doctor of pharmacy (PharmD) curriculum. DESIGN: Over 8 years, student pharmacists completed the StrengthsFinder assessment tool and identified their top 5 Signature Themes (talents). They then participated in either Web-based learning modules or live workshops designed to facilitate professional development. ASSESSMENT: Students preferred the live instruction over Web-based learning modules. Post-instruction evaluations demonstrated that students discussed their Signature Themes with peers, preceptors, and family members. Pharmacists working with students in strengths-related activities reported that the students applied the information in the practice setting. Both pharmacists and students recommended that this material be required for all students. CONCLUSIONS: Identifying a role in pharmacy that aligns with one's personal talents is critical for the success of pharmacy graduates. Strengths instruction is an important component of professional and career development, and can aid in identifying roles.